2018
DOI: 10.3144/expresspolymlett.2018.11
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing catalytic behavior of titanium complexes bearing bisphenolate ligands toward ring-opening polymerization of L-lactide and ε-caprolactone

Abstract: Abstract.A series of titanium complexes bearing substituted diphenolate ligands (RCH(phenolate) 2 , where R = H, CH 3 ,2, was synthesized and studied as catalysts for the ring opening polymerization of L-lactide and ε-caprolactone. Ligands were designed to probe the role of chelate effect and steric effect in the catalytic performance. From the structure of triphenolate (with one extra coordination site than diphenolate ligand) Ti complex, TriOTiO i Pr 2 , we found no additional chelation to influence the cata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…Diphenolate-supported mixed heterobimetallic Ti complexes [27]. Figure 14) [28]. The influence of the nature of the substituents on the ROP of -CL and L-LA was investigated Very recently, Chen et al disclosed the synthesis of a number of dinuclear titanium complexes supported by diphenolate ligands having various substituents on the methyne bridge ( Figure 14) [28].…”
Section: Ti-diphenolate Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…Diphenolate-supported mixed heterobimetallic Ti complexes [27]. Figure 14) [28]. The influence of the nature of the substituents on the ROP of -CL and L-LA was investigated Very recently, Chen et al disclosed the synthesis of a number of dinuclear titanium complexes supported by diphenolate ligands having various substituents on the methyne bridge ( Figure 14) [28].…”
Section: Ti-diphenolate Complexesmentioning
confidence: 99%
“…Figure 14) [28]. The influence of the nature of the substituents on the ROP of -CL and L-LA was investigated Very recently, Chen et al disclosed the synthesis of a number of dinuclear titanium complexes supported by diphenolate ligands having various substituents on the methyne bridge ( Figure 14) [28]. The influence of the nature of the substituents on the ROP of ε-CL and L-LA was investigated (Table 16).…”
Section: Ti-diphenolate Complexesmentioning
confidence: 99%
“…Terzopoulu et al [3] reported the ROP of CL using SO as a catalyst and initiator. Similarly, other novel initiators such as benzylalcohol [4,5], gelatin [6], lipase [7], mercaptohexanol [8], diethyleneglycol [9], bisphenolate ligand [10] and mPEG [11] were used for the ROP of CL. Due to the bio-degradability and bio-compatibility of PCL, it is used as a drug carrier material.…”
Section: Introductionmentioning
confidence: 99%
“…Organo aluminium complexes derived from anilines were used for the ROP of CL . In 2018, Jiang et al reported a novel catalyst for the ROP of CL . Galia and co‐workers studied the ROP of CL using wet β‐cyclodextrin as a novel catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…1 In 2018, Jiang et al reported a novel catalyst for the ROP of CL. 2 Galia and co-workers 3 studied the ROP of CL using wet β-cyclodextrin as a novel catalyst. Similarly, other catalysts such as ammoniumheptamolypdate, 4 cyclic trimeric phosphazene base, 5 phosphoricacid, 6 rare earth Schiff base complex, 7 silica compound, 8 zinc complex, 9 and functionalized aluminum alkoxide 10 were used as a catalyst for the ROP of CL.…”
Section: Introductionmentioning
confidence: 99%